Optimasi Hasil Produksi Olahan Daging Sapi Dengan Menggunakan Linear Programming (Studi Kasus : UD. Angkasa Timor Kupang) - Adoe, V S (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
ABSTRACTUD. Angkasa Timor is one of the business units engaged in beef processing with 3 forms of products produced, se'i, beef jerky and shredded beef. The obstacle faced is that entrepreneurs have not used the available resources optimally so the benefits have not been maximized. Therefore, this study aims to combine existing production resources so that entrepreneurs can obtain optimal production results and can obtain maximum profits. By using linear programming methods in the POM-QM For Windows V4 application, the analysis results are obtained X1 = 0.8571 kg, X2 = 1.8033 kg, and X3 = 0.2459 kg, with an Z value or an optimal profit of Rp. 7,197,893, Keywords : Linear Programming, Optimization